The End of Man - Martinon, Jean-Paul (punctum books, 2013)
Masculinity? This book attempts to answer this one-word question by revisiting key philosophical concepts in the construction of masculinity, not in order to re-write or debunk them again, but in order to provide a radically new departure to what masculinity means today. This new departure focuses on an understanding of sexuality and gender that is neither structured in oppositional terms (masculine-feminine, male-female, man-woman) nor in performative terms (for which the opposition remains always secretly in play), but in a perpendicular relation akin to that which brings space and time together. In doing so, this book doesn't aim to establish yet another theory within the field of masculism or men's studies, but to put forward a personal account of how a revised understanding of the relationship between space, time, and gender can thoroughly alter concepts of masculinity.